Characterization of persistent headache attributed to past stroke - André Rêgo; Rita Pinheiro; Sofia Delgado; Francisco Bernardo; Elsa Parreira (Arquivos de Neuro-Psiquiatria, 2022)
Background Persistent headache attributed to past stroke (PHAPS) is a controversial entity, recently included in the third edition of the International Classification of Headache Disorders (ICHD-3) despite being described only in retrospective studies.